Prediction of esophageal varices and variceal hemorrhage in patients with acute upper gastrointestinal bleeding. Issue 3 (March 2016) - Rockey, Don C; Elliott, Alan; Lyles, Thomas
Abstract : In patients with upper gastrointestinal bleeding (UGIB), identifying those with esophageal variceal hemorrhage prior to endoscopy would be clinically useful. This retrospective study of a large cohort of patients with UGIB used logistic regression analyses to evaluate the platelet count, aspartate aminotransferase (AST) to platelet ratio index (APRI), AST to alanine aminotransferase (ALT) ratio (AAR) and Lok index (all non-invasive blood markers) as predictors of variceal bleeding in (1) all patients with UGIB and (2) patients with cirrhosis and UGIB. 2233 patients admitted for UGIB were identified; 1034 patients had cirrhosis (46%) and of these, 555 patients (54%) had acute UGIB due to esophageal varices. In all patients with UGIB, the platelet count (cut-off 122, 000/mm 3 ), APRI (cut-off 5.1), AAR (cut-off 2.8) and Lok index (cut-off 0.9) had area under the curve (AUC)s of 0.80 0.82, 0.64, and 0.80, respectively, for predicting the presence of varices prior to endoscopy. To predict varices as the culprit of bleeding, the platelet count (cut-off 69, 000), APRI (cut-off 2.6), AAR (cut-off 2.5) and Lok Index (0.90) had AUCs of 0.76, 0.77, 0.57 and 0.73, respectively. Finally, in patients with cirrhosis and UGIB, logistic regression was unable to identify optimal cut-off values useful for predicting varices as the culprit bleeding lesion for any of the non-invasive markers studied. For all patients with UGIB, non-invasive markers appear to differentiate patients with varices from those without varices and to identify those with a variceal culprit lesion. However, these markers could not distinguish between a variceal culprit and other lesions in patients with cirrhosis.